1994
DOI: 10.1017/s0376892900024577
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Awareness through an Environmental Education Programme in the Atlantic Forest of Brazil

Abstract: Few environmental education programmes established in parks in Brazil have been formally evaluated. This paper describes the study of a school programme that was established to use formative evaluation to select and improve programme strategies, and employs summative evaluation to assess the effectiveness of the programme as a whole. The programme consisted of pre-visit strategies, such as a slide show and information given to teachers; on-site activities, which comprised Nature trails and a visitor centre; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 8 publications
0
32
0
3
Order By: Relevance
“…Some studies have found increases in both environmental knowledge and attitudes (Burrus-Bammel et al, 1980;Coleman & Lamond, 1993;Davis et al, 1980;Padua, 1994), while others have found increases in environmental knowledge but not in attitudes (Keen, 1991;Salt, 1993). Some studies which simply measured environmental attitudes have found small increases in those attitudes (Beckmann, 1989;Shepard & Speelman, 1985/86), whereas others have found no significant improvement (Eagles & Demare, 1995;Shepard & Speelman, 1985/86).…”
Section: Changing Environmental Attitudes and Behaviours By Environmementioning
confidence: 99%
“…Some studies have found increases in both environmental knowledge and attitudes (Burrus-Bammel et al, 1980;Coleman & Lamond, 1993;Davis et al, 1980;Padua, 1994), while others have found increases in environmental knowledge but not in attitudes (Keen, 1991;Salt, 1993). Some studies which simply measured environmental attitudes have found small increases in those attitudes (Beckmann, 1989;Shepard & Speelman, 1985/86), whereas others have found no significant improvement (Eagles & Demare, 1995;Shepard & Speelman, 1985/86).…”
Section: Changing Environmental Attitudes and Behaviours By Environmementioning
confidence: 99%
“…The separation of students in control or experimental group also avoids possibilities of experimental error. This design offers the same chance to both groups and exposes them to the same risks (PADUA, 1994). In this case, participating students in the Experimental Groups chose to take part in the trip, as it was constituent of the regular activities of their graduation program.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there can be an inference of the data obtained in this study to other populations whose realities are similar. Padua (1994) points out that the pre-test may influence the results, as it draws attention to determined topics which will again be asked, as well as it warns the interviewees on likely desirable responses, in case they know the objectives of the research. To minimize the influence, participants were not informed, in the moment of the pre-test, of the objectives of the research, nor were they induced on the relation between the test and the trip that would be carried out -what happened after the post-test only.…”
Section: Discussionmentioning
confidence: 99%
“…Susana Padua, for example, describes how conservationists succeeded in turning the Black Lion-tamarin from a pest into a source of pride and excitement for rural communities in Brazil (Padua 1994). Over the past years, the Mabuwaya Foundation tried to foster a sense of pride in the occurrence and conservation of the Philippine crocodile (Figure 3).…”
Section: Cultural Valuesmentioning
confidence: 99%